Técnicas grafo-plásticas y su influencia en el desarrollo de la motricidad fina - Valle Sànchez, Leidy Tatiana (2018)
The final report of the research project has the purpose of diagnosing the effect of the Graphical Plastic Technique on children's creativity, with which it is intended to encourage its originality, criticality, harmony with freedom. The development of this research is framed in the qualitative paradigm and is descriptive; corresponds to feasible projects that present an alternative to solve the problem; it is based on documentary, bibliographical and field research. Their techniques to obtain information are: observation, survey, instrument, questionnaire, observation card. We worked in a population of 46 students and 4 teachers. During the development of the theme, emphasis is placed on creativity, as a guideline for research. Through this research it is possible to determine the need to plan the creation of a Didactic Guide of Graphical Techniques.